Pinhole imaging to observe spatial jitters of a triple-pulse X-ray source on the Dragon-II LIA - Wang, Yi; Yang, Zhi-Yong; Jing, Xiao-Bing; Li, Qin; Ding, Heng-Song; Dai, Zhi-Yong (Nuclear science and techniques, 2016)
In high-energy flash radiography, scattered photons degrade the acquiring image, which limits the resolving power of interfaces and density of dense object. The application of large anti-scatter grid can reduce the scattered photons remarkably, but this requires a stable source position in order to reduce the loss of signal photons in the grid structure. The pinhole imaging tech-nique is applied to observe spatial jitters of a triple-pulse radiographic source of a linear induction accelerator. Numerical simulations are conducted to analyze the imaging performance with the same or close parameters of the pinhole object and experimental alignment. Experi-ments are carried out to observe spatial jitters of the source between different measurements. Deviations of the source position between different pulses are measured in each experiment.